Dual role for inositol‐requiring enzyme 1α in promoting the development of hepatocellular carcinoma during diet‐induced obesity in mice. Issue 2 (21st May 2018) - Wu, Ying; Shan, Bo; Dai, Jianli; Xia, Zhixiong; Cai, Jie; Chen, Tianwei; Lv, Songya; Feng, Yuxiong; Zheng, Ling; Wang, Yan; Liu, Jianfeng; Fang, Jing; et al.
Abstract : Obesity is associated with both endoplasmic reticulum (ER) stress and chronic metabolic inflammation. ER stress activates the unfolded protein response (UPR) and has been implicated in a variety of cancers, including hepatocellular carcinoma (HCC). It is unclear whether individual UPR pathways are mechanistically linked to HCC development, however. Here we report a dual role for inositol‐requiring enzyme 1α (IRE1α), the ER‐localized UPR signal transducer, in obesity‐promoted HCC development. We found that genetic ablation of IRE1α in hepatocytes not only markedly reduced the occurrence of diethylnitrosamine (DEN)‐induced HCC in liver‐specific IRE1α knockout (LKO) mice when fed a normal chow (NC) diet, but also protected against the acceleration of HCC progression during high‐fat diet (HFD) feeding. Irrespective of their adiposity states, LKO mice showed decreased hepatocyte proliferation and signal transducer and activator of transcription 3 (STAT3) activation, even in the face of increased hepatic apoptosis. Furthermore, IRE1α abrogation blunted obesity‐associated activation of hepatic inhibitor of nuclear factor kappa B kinase subunit beta (IKKβ)‐nuclear factor kappa B (NF‐κB) pathway, leading to reduced production of the tumor‐promoting inflammatory cytokines tumor necrosis factor (TNF) and interleukin 6 (IL‐6). Importantly, higher IRE1α expression along with elevated STAT3 phosphorylation was also observed in the tumor tissues from human HCC patients, correlating with their poorer survival rate. Conclusion : IRE1α acts in a feed‐forward loop during obesity‐induced metabolic inflammation to promote HCC development through STAT3‐mediated hepatocyte proliferation. (Hepatology 2018).